State-of-the-art of Esophagectomy for Cancer: From Open to Laparoscopic and Robotic Technique - Coco, Danilo; Leanza , Silvana (Open Access Macedonian Journal of Medical Sciences, 2020)
INTRODUCTION: The results for the meta-analytical review, which contrasted laparoscopic or robotically assisted esophagectomy for cancer against open esophagectomy (OE), indicated feasibility and safety associated with the robotic method. AIM: The objective of this study is to review the current literature on MIE (Laparo-thoracoscopic and Robotic approach) and open approach and check the state-of-the-art of esophagectomy for cancer. MATERIALS AND METHODS: The comparison of studies which contrasted laparoscopic or robotically assisted esophagectomy for cancer against open esophagectomy (OE). RESULTS: This review represented the largest sequence of mini-invasive esophagectomy (MIE) to date and the results appear to be comparable to those attained by the traditional open approach. MIE constitutes a safe procedure with a learning curve of around 36 cases. CONCLUSION: The studies did not reveal variations in mortality and morbidity rate, conversion rate, intensive care unitstay, 1-month mortality, and post-operative complications between the mini-invasive esophagectomy cohort and OE cohort.